The Influence of Accounting Understanding, Financial Inclusion, and Social Environment on Savings Behavior Among MSME Actors in Selong City - Muhammad Aldi Losa; A.M. Maturidi (Danadyaksa: Post Modern Economy Journal, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, yet most MSME actors exhibit low saving behavior. This study examines the influence of accounting understanding, financial inclusion, and social environment on saving behavior among MSME actors in Selong City, East Lombok Regency. Using a quantitative associative approach, data were collected from 95 respondents through a Likert-scale questionnaire. Multiple linear regression analysis was employed to test the hypotheses, after validating the instrument with corrected item-total correlation (r-table = 0.202) and reliability with Cronbach’s alpha (>0.60). Classical assumption tests (normality, multicollinearity, heteroscedasticity) were satisfied. The results show that simultaneously, accounting understanding, financial inclusion, and social environment have a significant effect on saving behavior (F = 51.564, p = 0.000, adjusted R² = 0.653). Partially, financial inclusion has a positive and significant effect (β = 0.770, p = 0.000), and the social environment also has a positive and significant effect (β = 0.268, p = 0.001). However, accounting understanding does not have a significant effect (β = -0.050, p = 0.180). This indicates that access to formal financial services and socio-ecological support are more dominant in shaping saving habits than accounting knowledge alone in traditional MSMEs. The study concludes that expanding financial inclusion through digital agents and strengthening community-based social capital are effective strategies. Future research should include additional variables such as income and self-control.